Dual electrochemical and chemical control in atom transfer radical polymerization with copper electrodes. Issue 20 (5th May 2022) - De Bon, Francesco; Lorandi, Francesca; Coelho, Jorge F. J.; Serra, Armenio C.; Matyjaszewski, Krzysztof; Isse, Abdirisak A.
Abstract : The use of a Cu cathode in e ATRP allows exploiting the synergistic effect between electrochemical and chemical stimuli to halt or accelerate polymerizations, reduce energy consumption and achieve control in challenging systems. Abstract : In Atom Transfer Radical Polymerization (ATRP), Cu 0 acts as a supplemental activator and reducing agent (SARA ATRP) by activating alkyl halides and (re)generating the Cu I activator through a comproportionation reaction, respectively. Cu 0 is also an unexplored, exciting metal that can act as a cathode in electrochemically mediated ATRP ( e ATRP). Contrary to conventional inert electrodes, a Cu cathode can trigger a dual catalyst regeneration, simultaneously driven by electrochemistry and comproportionation, if a free ligand is present in solution. The dual regeneration explored herein allowed for introducing the concept of pulsed galvanostatic electrolysis (PGE) in e ATRP. During a PGE, the process alternates between a period of constant current electrolysis and a period with no applied current in which polymerization continues via SARA ATRP. The introduction of no electrolysis periods without compromising the overall polymerization rate and control is very attractive, if large current densities are needed. Moreover, it permits a drastic charge saving, which is of unique value for a future scale-up, as electrochemistry coupled to SARA ATRP saves energy, and shortens the equipment usage.